Pelatihan Membaca Puisi Sesuai dengan Kaidah Bahasa Indonesia bagi Siswa Madrasah - Mardiah Mardiah; Hendro Lisa; Martina Napratilora; Rika Devianti; Dina Liana (ABDIMASY: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2021)
Reading poetry is one of the language skills, the skills are reading poetry in public with correct pronunciation, beautiful intonation, and correct expression. However, especially students at MI Nurul Huda Sungai Binjai, Keritang District did not read poetry by applying the conditions or rules for reading poetry. For instance: not reading poetry with the correct pronunciation, not using beautiful intonation, also not expressing the poetry properly. Thus, the training was given to students to read poetry properly. The method used in this service is the training method. The result of this training indicated that students able to read poetry with correct pronunciation, beautiful intonation, and they can read poetry with correct expressions.